Schools Traffic Noise Pollution Levels Along Federal Roads in Muallim District, Perak, Malaysia. Issue 1 (January 2022) - Nayan, N; Hashim, M; Saleh, Y; Mahat, H; Luyan, M H; Juanis, J; Khotimah, N
Abstract: This article aims to identify the school traffic noise level along federal roads in Muallim District, Perak, namely SMK Khir Johari (SMKKJ), SMK Agama Slim River (SMKASR) and SMK Dato' Zulkifli Muhammad (SMKDZ). Data were collected during school hours and on weekends, from 7 September to 13 September 2019 and three times a day, 7.00 -8.00 am, 9.00 -10.00 am and 12.00 -1.00 pm. Data was collected using Digital Sound Level Meter AS804, which was mounted on a tripod approximately one meter high from the road surface to prevent road sound reflection. Sound recordings were performed using decibel scale weights (dBA) and values for Max (Maximum Noise Level), Min (Minimum Noise Level), Leq (Average Overall Noise) with five minutes time delay and descriptive analysis. The findings show all stations values exceeded the standards set by the Malaysia Department of Environment (DOE) (60 dBA). SMKKJ shows the Min value is 57.7 dBA, the Max value is 94.5 dBA and Leq 76.1 dBA during working hours. In conclusion, the study showed that all stations recorded high noise during working hours and non-working hours surpass the standard set by DOE during the day. The need for the Malaysian Ministry of Education to assess and plan to reduce this noise level through short-term and long-term measures.